PENGARUH KEBIJAKAN MENPAN TERHADAP KINERJA PELAYANAN PUBLIK - Zakiyah, Said (Pusjar SKPP Lembaga Administrasi Negara, 2007)
Weaken of straightening law for implementing policy which has been specified causing the policy does not walk on the way. This condition happened at various sector, also at the public service. The research aim is to know the implementation of Regulation of National Empowerment of Apparatus Ministry (“PERMENPAN”) especially number 25 and 26 Year 2006 through performance of public service, implementation of some approach of management quality methods and innovation and the effort of local government to improve the public services quality. With analytical descriptive method which supported by secondary data from various sources can be concluded that PERMENPAN number 25 and 26 had effect to improve the performance of public service, the public services unit that implemented management quality methods and innovations and efforts of local government to improve the public services Keywords: Implementation, Public Services, Performance of Public Services, Public Service Quality, Innovation